EVALUASI KINERJA POMPA PENDINGIN PRIMER RSG-GAS SETELAH BEROPERASI 27.000 JAM OPERASI - Suroso, Suroso (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
The cooling system of MTR GA. Siwahessy consists ofprimary cooling system and secondary coolingsystem which are equiped with several i. e.pumps are primary pump and secondary pump. The pumps are veryimportancefor supporting reactor operation. The reactor has beenoperatedmore than 27,000 hours since thefirst time operation on 1987, so theperformance primary pump need to be evaluated. The evaluation is basedonmeasurement results inthefield. The evaluation results ofpump performance ispresented bycharacteristiccurve consisting of: head, efficiency and pump power as the junction of flow rate capacity. The primarycooling pump characteristics after 27,000 hours in operation show that by increasing of head andpumppower, the power supply is still able overcome and still under its specified value i.e. 160kW. The deviation ofhead, pump power and efficiency compared the commissioning condition is less than 10 %. so the primarvpumpperformance is still good.